2021
DOI: 10.52131/joe.2021.0302.0037
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of Renewable Energy Consumption, Economic Growth, Population Growth, FDI, and Environmental Degradation in South Asian Countries: New Evidence from Driscoll-Kraay Standard Error Approach

Abstract: Environmental degradation is the most prominent area nowadays, especially in developing counties where high renewable energy consumption and population growth deteriorate the atmosphere of the country. Thus, the current study investigates the nexus among renewable energy consumption, economic growth (EG), population growth, foreign direct investment (FDI), and environmental degradation in South Asian countries. The covariance matrix estimators that are developed by “Driscoll and Kraay” are used in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The results showed that technology adoption has a positive link with ES. These results are supported by Nathaniel, Yalçiner, and Bekun (2021); (Shah, Hussain, Nawaz, & Iqbal, 2021;Wenlong et al, 2022), which claims that the tendency of firms to adopt new technologies enables them to address and mitigate environmental issues and sustains environmental productivity. These results are also in line with the study of Jimoh and Lin (2019).…”
Section: Discussionmentioning
confidence: 82%
“…The results showed that technology adoption has a positive link with ES. These results are supported by Nathaniel, Yalçiner, and Bekun (2021); (Shah, Hussain, Nawaz, & Iqbal, 2021;Wenlong et al, 2022), which claims that the tendency of firms to adopt new technologies enables them to address and mitigate environmental issues and sustains environmental productivity. These results are also in line with the study of Jimoh and Lin (2019).…”
Section: Discussionmentioning
confidence: 82%
“…Keeping in view the above arguments regarding the efficacy of environmental policies, energy productivity and environmental management technologies in preventing climate changes and CO 2 concentrations, the basic goal of the study is to analyze the impact of these factors on environmental pollution in Indonesia. Indonesia is an interesting case study as it is one of the top polluting countries in the world and occupies the sixth position among the top ten highest green house gas emitter countries (Shah et al, 2021;Sohail et al, 2022). By the end of year 2019 before the COVID-19 outbreak, Indonesia was among the world's rapidly growing emerging markets.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the seven emerging ASEAN financial markets are operating, and these are Bursa Malaysia, the Ho Chi Minh Exchange, the Hanoi Stock Exchange, the Indonesia Stock Exchange, the Singapore Stock Exchange, The Philippine Stock Exchange, and the Stock Exchange of Thailand. Due to the distinctive regional feature, investors can access the capital markets and benefit from investment opportunities ranging from sophisticated products in mature countries like Singapore to frontier economies like Vietnam (La Torre, Mango, Cafaro, & Leo, 2020;Shah, Hussain, Nawaz, & Iqbal, 2021). Over 3,400 firms were combined with a market capitalization of USD 2.9 trillion on the regional exchanges in 2020.…”
Section: Introductionmentioning
confidence: 99%